Self Disclosure pada Remaja Penyintas Verbal Abuse di Panti Asuhan X - Sipahutar, Christina Putri Ben; Kristinawati, Wahyuni (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study explored adolescents who experienced verbal abuse to find out how self-disclosure is portrayed in adolescent verbal abuse survivors. This research uses qualitative methods with a case study approach. Data collection techniques in this study used observation methods and interviews conducted to main sources and significant others. The main informants in this study were two teenagers who experienced verbal abuse committed by staff at the orphanage. The results showed that both adolescents consciously carried out self-disclosure to reduce the pressure received but only to the closest people and trusted by both sources. Both research sources explained that at least each of them needed time and consideration before self-disclosure about verbal abuse experienced. Although they have told about the events experienced, both revealed that there are still parts that are hidden from others because of feelings of fear of being blasphemed and also feel unprepared to burden more people.